Answer :

= (x + 1)(x-4)(x + 3)(x-6) + 24


= (x2-4x + x-4)(x2–6x + 3x-18) + 24


= (x2-3x-4)(x2–3x-18) + 24


Let x2 – 3x = a


= (a-4)(a-18) + 24


= a2-18a-4a + 72 + 24


= a2-22a + 96


= a2-16a-6a + 96


= a(a-16)-6(a-16)


= (a-6)(a-16)


Putting back the values of a we get,


= (x2 – 3x -6)( x2 – 3x -16)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

I/we factorise thWest Bengal - Mathematics

I/we factorise thWest Bengal - Mathematics

I/we factorise thWest Bengal - Mathematics

I/we factorise thWest Bengal - Mathematics

Let’s resolve intWest Bengal - Mathematics

Let’s resolve theWest Bengal - Mathematics

Let’s resolve theWest Bengal - Mathematics

Let’s resolve intWest Bengal - Mathematics

Let’s resolve intWest Bengal - Mathematics

Let’s resolve intWest Bengal - Mathematics